2011
DOI: 10.1371/journal.pone.0023299
|View full text |Cite
|
Sign up to set email alerts
|

Association between Walking Speed and Age in Healthy, Free-Living Individuals Using Mobile Accelerometry—A Cross-Sectional Study

Abstract: ContextWalking speed is a fundamental parameter of human motion and is increasingly considered as an important indicator of individuals' health status.ObjectiveTo evaluate the relationship of gait parameters, and demographic and physical characteristics in healthy men and women.Design, Setting, and ParticipantsRecruitment of a subsample (n = 358) of male and female blood donors taking part in the Cambridge CardioResource study. Collection of demographic data, measurement of physical characteristics (height, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 33 publications
(43 reference statements)
9
94
2
1
Order By: Relevance
“…About 26%, 56%, 74% and 80% of the interviewed households had a network distance to the nearest wet market or supermarket of less than 0.5 km, 1.0 km, 1.5 km and 2.0 km, respectively (Table 8). Assuming a median walking speed for an adult of 4.5 km/h or 1.25 m/s [51], and a 15-min walk as the commonly accepted walking time in food studies [36,52], then anything up to about 1.1 km is an acceptable walking distance.…”
Section: Wet Market Planning Policiesmentioning
confidence: 99%
“…About 26%, 56%, 74% and 80% of the interviewed households had a network distance to the nearest wet market or supermarket of less than 0.5 km, 1.0 km, 1.5 km and 2.0 km, respectively (Table 8). Assuming a median walking speed for an adult of 4.5 km/h or 1.25 m/s [51], and a 15-min walk as the commonly accepted walking time in food studies [36,52], then anything up to about 1.1 km is an acceptable walking distance.…”
Section: Wet Market Planning Policiesmentioning
confidence: 99%
“…It concluded that distance covered by the individual was decline as the age increases. [18] As the age increases, walking speed of individual was decrease. Hence, PCI was increase and distance covered by individual was also reduced that required more energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…The study done by Michaela Schimpl supports this study as a negative relationship between BMI and walking parameter distance is consistent with the findings of Levine. [18] As the difference in the resting HR and post immediate test HR increases, PCI increases. The previous study also supported this study.…”
Section: Discussionmentioning
confidence: 99%
“…2464 rapid clinical functional tests (Table 1) performed by 224 elderly women with osteoporosis (mean age 68.3 +/-7.7 years old) were collected in 4 European centers in France, Germany, Italy and Switzerland using a high precision 3D accelerometer [8][9][10] developed at the Sylvia Lawry Center for Multiple Sclerosis Research (SLCMSR), Munich. The data collection started in July 2010 and the SLCMSR database was internally freeze for exploratory analysis in December 2011; however, collection and transfer of new actibelt ® data continued in parallel.…”
Section: Data and Subjectsmentioning
confidence: 99%